A multi-dimensional approach for managing open innovation in NPD. Issue 10 (2nd October 2017) - Bahemia, Hanna; Squire, Brian; Cousins, Paul
Abstract : Purpose: This paper explores openness within new product development (NPD) projects. The purpose of this paper is to examine the impact of breadth, depth and partner newness on product innovativeness and product competitive advantage. The authors also seek to examine the contingent effects of the appropriability regime. The authors make suggestions to academics and practitioners based on the findings. Design/methodology/approach: The authors use a structured survey instrument producing an empirical analysis of 205 NPD projects in the manufacturing sector in the UK. The authors use an ordinary least squares regression model to test hypothesised relationships between openness (breadth, depth and partner newness), product innovativeness, product competitive advantage and the appropriability regime. Findings: The authors find that each of the three dimensions of openness, depth, breadth and partner newness, have a significant but differing impact on product innovativeness. Specifically, the study indicates that breadth has a positive effect but only in the presence of a strong appropriability regime, partner newness has a direct positive effect, and depth a direct negative effect. The authors also find that product innovativeness has a positive impact on product competitive advantage. Research limitations/implications: Further research should focus on replicating the findings in other countries, search for further moderating factors, such as the stage of the NPD process, and analyse the longitudinal impact of openness within NPD projects. Practical implications: Organisations are encouraging managers to be more open in their approach to NPD. The authors' findings suggest that managers need to think about the three dimensions of openness, breadth, depth and partner newness. Their engagement with each of these dimensions depends on the desired outcomes of the innovation project and the strength of patents. Originality/value: The research extends the extant supplier involvement in new product development literature to examine the effect of up to 11 types of external actor in NPD projects. The authors test a new multi-dimensional measurement scale for the openness construct. The authors show that each dimension has a different relationship with product innovativeness.